Analisis Perbandingan Efisiensi Buck-Boost Converter Dengan Cuk Converter Pada Panel Surya - Tanika Berliana Ghaisa Azmi; Aryadhana Putra Susanto; Ahmad Nauval Zakariya; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2024)
Solar energy is an alternative energy source that is increasingly popular in various places because it never runs out and is environmentally friendly. The application of solar energy that is commonly used today is solar panels. However, solar panels only produce electrical energy at a relatively low voltage. Therefore, a tool is needed that can increase the electrical voltage produced by solar panels so that they can be used optimally. In this case, Buck-Boost Converter and CUK Converter are two types of converters that can be used. Buck-Boost Converter is a type of converter that can change the input DC voltage into an output DC voltage with a value that is higher or lower than the input voltage. Buck-Boost Converters are suitable for use on solar panels that produce fluctuating voltage. Meanwhile, the CUK Converter is a type of converter that can also change the input DC voltage to an output DC voltage, the same as Buck-Boost but with a simpler design. However, the weakness of the CUK Converter is that its performance is worse when the electrical load changes. When used on solar panels, both types of converters can be used depending on the needs and conditions of the solar panels used. If the solar panel produces a fluctuating voltage, then a Buck-Boost Converter can be used to produce a stable output voltage. However, if the solar panel produces a stable voltage, then the CUK Converter can be used as a simpler alternative